2004
DOI: 10.1007/s00204-004-0593-9
|View full text |Cite
|
Sign up to set email alerts
|

Vascular wall damage in rats induced by methidathion and ameliorating effect of vitamins E and C

Abstract: We examined the effect of subacute methidathion (MD) administration on vascular wall damage and evaluated the ameliorating effects of combination of vitamins E and C against MD toxicity. The experimental groups were: rats treated with corn oil (control group), rats treated with 5 mg/kg MD (MD), and rats treated with 5 mg/kg body weight MD plus vitamin E and vitamin C (MD+Vit). The groups were given MD by gavage on 5 days a week for 4 weeks at a daily dose 5 mg/kg (MD and MD+Vit) using corn oil as the vehicle. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 21 publications
2
42
0
Order By: Relevance
“…By washing erythrocytes three times in cold isotonic saline (0.9%, w/v), erythrocyte packets were prepared and used to assay for MDA concentrations using the doubleheating method of Draper and Hadley [26], as modified by [27]. The principle of the method was based on spectrophotometric measurement of the colour pro- , and expressed in nanomoles per gram of haemoglobin.…”
Section: Determination Of Erythrocyte Malondialdehyde Concentrationmentioning
confidence: 99%
“…By washing erythrocytes three times in cold isotonic saline (0.9%, w/v), erythrocyte packets were prepared and used to assay for MDA concentrations using the doubleheating method of Draper and Hadley [26], as modified by [27]. The principle of the method was based on spectrophotometric measurement of the colour pro- , and expressed in nanomoles per gram of haemoglobin.…”
Section: Determination Of Erythrocyte Malondialdehyde Concentrationmentioning
confidence: 99%
“…Some experimental studies have demonstrated that vitamins C and E can be used to counteract pesticide toxicity (Yavuz and Kutsal, 2004;Yousef et al, 2006). Vita- min C is an important water-soluble chain-breaking antioxidant and enzyme cofactor (Wilson, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…-tocopherol (Vitamin E) is the major lipid soluble antioxidant and is known to protect cellular membranes and lipoproteins from peroxidation (Yavuz et al, 2004). -Tocopherol inhibits free radical formation (Kalender et al, 2004) and can effectively minimize lipid peroxidation (Traber and Atkinson, 2007).…”
Section: Introductionmentioning
confidence: 99%